Banning Correctional Facility: Residential substance abuse treatment program process survey - Hulvey, Melinda DeAnn (2000)
The purpose of this study is to examine more closely those program components which facilitate dissonance, disharmony, and ambiguity among the keygroups of a residential substance abuse treatment program